Isolation of the tomato AGAMOUS gene TAG1 and analysis of its homeotic role in transgenic plants. - Pnueli, L (1994)
To understand the details of the homeotic systems that govern flower development in tomato and to establish the ground rules for the judicious manipulation of this floral system, we have isolated the tomato AGAMOUS gene, designated TAG1, and examined its developmental role in antisense and sense transgenic plants. The AGAMOUS gene of Arabidopsis is necessary for the proper development of stamens and carpels and the prevention of indeterminate growth of the floral meristem. Early in flower development, TAG1 RNA accumulates uniformly in the cells fated to differentiate into stamens and carpels and later becomes restricted to specific cell types within these organs. Transgenic plants that express TAG1 antisense RNA display homeotic conversion of third whorl stamens into petaloid organs and the replacement of fourth whorl carpels with pseudocarpels bearing indeterminate floral meristems with nested perianth flowers. A complementary phenotype was observed in transgenic plants expressing the TAG1 sense RNA in that first whorl sepals were converted into mature pericarpic leaves and sterile stamens replaced the second whorl petals.